Michel Foucault: Sejarahwan Spesifik Masa Kini - Konrad Kebung (Studia Philosophica et Theologica, 2020)
The paper presents Foucault’s rich historical analyses on various past historical events which he claimed to be the hidden historical materials. Using the archaeological method, particularly on his early works, he tried to dig out all these facts through various archives to see how people in different historical periods thought about them and took action on them. Through such analyses many people consider him to be a historian. However, he is not an historian understood in the traditional sense of the word, but a specific historian, namely the historian of the present.